Suitability of wheat flour blends with malted and fermented cowpea flour for noodle making - Ritika, B.Y. (2017)
The current trend is to develop composite flours based food products with enhanced nutritional as well as other superior quality traits adding variety to the food basket. Composite flour noodles were developed using blends of refined wheat flour with malted and fermented cowpea flour with replacement level of 10 and 20%. The native flours and their blends were analyzed for physicochemical, functional and pasting properties to assess their suitability for noodle making. The results of the proximate composition showed that malting and fermentation enhanced the protein content of the cowpea flour. Increasing the level of malted or fermented cowpea flour in the blend resulted in the increased protein content and water absorption capacity. The pasting properties of the refined wheat flour also got altered after supplementation with cowpea flour. The noodles were analyzed for cooking properties including cooking time, cooking loss and cooked weight. The textural attributes of the cooked noodles were determined using food texture analyzer. Composite flour noodles revealed less cooking time, less percent solid loss, low hardness, adhesiveness and cohesiveness but increased cooking yield. Presence of ingredients other than wheat flour could have caused discontinuity in the gluten network. resulting in the faster moisture penetration and hence less optimum cooking time of noodles. Noodles with improved nutritional and acceptable cooking and textural quality attributes can be successfully developed using composite flours based upon refined wheat flour and malted cow pea flours.